CHEMICAL AND MICROBIOLOGICAL STUDY FOR THE WATERS OF LAKE BRӐTENI - Alin-Marius NICULA; Katja BUROW; Erika KOTHE; Cristina ROŞU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The present paper is a study of the water quality sampled from Brăteni Lake and the streams near the lake. The analysis targets the microbiology via DNA extraction, PCR and sequencing of DNA fragments and the chemistry through nitrate and ammonium determination. For the quantification of bacteria present in water samples, 3 culture media were used: R2A for oligotrophic microorganisms, Standard I as a complete medium and Burks for nitrogen fixing bacteria enrichment. The identified bacteria included, Pedobacter, Streptomyces, Bacillus, Flavobacterium and Sphingobacterium. Nitrate and ammonium had higher concentrations in one of the streams near the lake. The results highlighted a close link between land use and lake water quality, agricultural activity having a strong influence on water quality.